ANALYSIS OF THE HISTOLOGICAL STUDY OF THE INFLUENCE OF THE BREAST IMPLANT SHELL ON THE SURROUNDING TISSUES IN THE EXPERIMENT - Iryna M. Shmyhina; Yurii D. Pidchenko; Oleksandr V. Khrapach; Vasyl V. Khrapach (Клінічна та профілактична медицина)
Introduction. Breast implants are widely used for cosmetic augmentation and reconstruction of the breast after mastectomy. Today, many types of breast implants are available, which differ in different physical characteristics, such as shape, size, gel material and surface texture, and also differ in the chemical composition of the implant components, such as the elastomeric shell.